Correlation between explosive strength, aerobic power and repeated sprint ability in elite basketball players - Stojanovic, M. D.; Ostojic, S. M.; Calleja-Gonzalez, J.; Milosevic, Z.; Mikic, M. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: The aim of this study was to examine the relationship between explosive strength and aerobic power with basketball-specific repeated sprint ability in elite male basketball players. METHODS: Twenty-four elite basketball players (age 22.2±3.4 years, height 197.1±6.2 cm, weight 95.7±8.8 kg; training experience 11.0±3.1 years; mean±SD), participated in the study. Subjects performed countermovement jump (CMJ) test and incremental pseudo-ramp test protocol with measured CMJ height and VO2max, respectively. Specific repeated sprint ability (RSA) test was conducted, with total sprinting time (summation of 10 sprint times - RSAtot) and sprint decrement (fatigue index - RSAFI) calculated. RESULTS: Significant decrements in sprint performance from the eight 30-m sprint (PCONCLUSION: CMJ is a predictor of RSA in elite basketball players. It seems that coaches and strength and conditioning professionals should devote additional time for explosive strength development in elite basketball players during preparatory period to enhance RSA performance.